L’accès des femmes aux postes-cadres : un défi pour les entreprises d’assurance - Dumont, Monique (Assurances)

(untitled) (HEC Montréal, 1982)
Women status has changed since the end of the second World War. After an outlook of the evolution of women in the Canadian society, particularly in Quebec, the author analyses the new generation of women which is emerging: the career women. That new type of women is a challenge for the insurance industry: it will have to integrate women to their executive staff.